2019
DOI: 10.1515/cclm-2019-0996
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of 25(OH)-vitamin D and 24,25(OH)2-vitamin D to define cut-offs for CYP24A1 mutation and vitamin D deficiency in a population of 1200 young subjects

Abstract: BackgroundSimultaneous measurement of 25(OH)D and 24,25(OH)2D is a new tool for predicting vitamin D deficiency and allows evaluating CYP24A1 lack of function. Interpretation of 24,25(OH)2D should be performed according to 25(OH)D levels and a ratio, called the vitamin D metabolite ratio (VMR) has been proposed for such a purpose. Unfortunately, the VMR can be expressed in different ways and cannot be used if 24,25(OH)2D concentrations are undetectable. Here, we propose evaluating the enzyme activity taking in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…There were no changes in the vitamin D metabolite ratios, which are considered as surrogate markers of the hydroxylation enzymes CYP27B1 and CYP24A1. (27,34) FGF23 reduces CYP27B1 activity and increases CYP24A1 activity leading to a reduction in 1,25(OH)2D in favor of increased production of 24,25(OH)2D; whereas PTH increases CYP27B1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…There were no changes in the vitamin D metabolite ratios, which are considered as surrogate markers of the hydroxylation enzymes CYP27B1 and CYP24A1. (27,34) FGF23 reduces CYP27B1 activity and increases CYP24A1 activity leading to a reduction in 1,25(OH)2D in favor of increased production of 24,25(OH)2D; whereas PTH increases CYP27B1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cavalier et al has suggested that the parallel analysis of these two metabolites facilitates an assessment of vitamin D metabolism that is based on dynamic physiologic principles. In particular, the proportion of 25(OH)D and 24,25(OH) 2 D 3 takes the individual set-point for vitamin D sufficiency into account, and may thus detect early functional vitamin deficiencies [ 30 ]. The 25,26(OH) 2 D was recently brought into connection with intestinal calcium transport.…”
Section: Introductionmentioning
confidence: 99%
“…It also means that when sufficient amounts of biologically active vitamin D are available, CYP24A1 is upregulated, and more 24,25(OH) 2 D is formed [ 28 , 29 ]. This approach could lead to a better personalization of vitamin D supplementation [ 30 ]. Nevertheless, measurement of 24,25(OH) 2 D and VMR (vitamin D metabolite ratio of serum, 24, 25(OH) 2 D to 25(OH)D) values are available only to clinical laboratories equipped with LC-MS capabilities in the absence of available automated immunoassays.…”
Section: Methodsmentioning
confidence: 99%
“…It also means that when sufficient amounts of biologically active vitamin D are available, CYP24A1 is upregulated, and more 24,25(OH) 2 D is formed [28,29]. This approach could lead to a better personalization of vitamin D supplementation [30]. Nevertheless, measurement of 24,25(OH)…”
Section: Other Vitamin D Metabolites As Markers Of Vitamin Status?mentioning
confidence: 99%